Vrem realism, nu magie! Disputa în jurul cronicilor teatrale din revista Útunk (Anul 1954) - György, Andrea (Theatrical Research, 2020)
We Want Realism, Not Magic! The Dispute Over Theatre Criticism in Útunk in 1954 After the communist took power in the aftermath of World War II, the political leadership set out to impose a new concept of the world and a new kind of man. In this sense, it was necessary to gain control over the cultural press, subordinating the practices of criticism to Marx- ist propaganda, turning into a means of manipulating readers. Criticism, like fiction, was considered a deed, and in the party`s view, the critic was to play an important role in shaping the new society. Focusing on the dispute over theatre criticism that took place in the Útunk magazine in 1954, my goal was to identify how critical discourse about theatre worked in this period.